Syntheses, characterization and properties of three coordination polymers with interpenetrating structures comprising 4, 4′-(1H-1, 2, 4-triazol-1-yl)methylene-bis(benzonic acid). Issue 69 (4th December 2019) - Zhao, Lun; Meng, Lingshu; Liu, Xin; Guo, Guanlin; Xiao, Congcong; Liu, Haibing
Abstract : The synthesis and characterization of three compounds with H2 tmdb ligands is reported. The polymers were analyzed using PXRD, IR, TGA and fluorescence spectrometry. Abstract : Three new coordination polymers (CPs), [Pb(tmdb)](H2 O) n (1 ), [Zn(tmdb)(bimb)0.5 ] n (2 ) and [Zn3 (tmdb)3 (bpmb)1.5 ](H2 O)6 n (3 ) (H2 tmdb = 4, 4′-(1 H -1, 2, 4-triazol-1-yl)methylene-bis(benzonic acid), where bpmb = 1, 4-bis(pyridin-4-ylmethoxy)benzene and bimb = 1, 4-bis(imidazoly-1-yl)benzene), have been solvothermally or hydrothermally synthesized. Compound 1 is a 2D network with the point symbol (4·6·8)(4·6 2 ) and compound 2 is a 4-fold interpenetrating 3D network with spiral chains. The topological type of 2 is dmc (topos&RCSR.ttd) with the point symbol (4·8 2 )(4·8 5 ). Compound 3 is a 3-fold interpenetrating 3D network with the point symbol (6 3 )2 (8·6 5 )2 (10·6 2 )(8·10·6 4 ). The electrochemiluminescence (ECL) behaviors of 2 and 3 were studied. The applications of CP 2 and 3 in detecting ions were explored, and the results show that they can be used as fluorescent probes to selectively detect and identify Fe 3+ ions in water. In addition, the applications of CP 2 and 3 in the adsorption and separation of dyes were researched. Furthermore, the gas adsorption of 3 was studied.